1997
DOI: 10.1111/j.1432-1033.1997.00306.x
|View full text |Cite
|
Sign up to set email alerts
|

Inositol Phospholipid 3‐Kinase is Activated by Cellular Stress but is not Required for the Stress‐Induced Activation of Glucose Transport in L6 Rat Skeletal Muscle Cells

Abstract: A characteristic response of cells subjected to a stress stimulus is a rapid activation of cellular glucose transport. The mechanisms governing this increase in glucose transport are poorly understood, but it has been suggested that the response may involve the intracellular-signaling components that also participate in the hormonal activation of glucose transport. In skeletal muscle and fat tissue, inositol phospholipid 3-kinase plays an integral role in the regulation of both basal and insulin-stimulated glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 38 publications
3
20
0
Order By: Relevance
“…At least part of these effect are believed to be caused by the ability of trivalent arsenic to bind to SH groups of important cellular (signaling) proteins. Both sodium arsenite and arsenic trioxide can activate PI3K and/or the MAPK family members p44/p42 MAPK, SAPKs/ JNKs, and p38 (48,49). We demonstrated that these kinases were indeed activated by sodium arsenite in OVCAR-3 cells.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…At least part of these effect are believed to be caused by the ability of trivalent arsenic to bind to SH groups of important cellular (signaling) proteins. Both sodium arsenite and arsenic trioxide can activate PI3K and/or the MAPK family members p44/p42 MAPK, SAPKs/ JNKs, and p38 (48,49). We demonstrated that these kinases were indeed activated by sodium arsenite in OVCAR-3 cells.…”
Section: Discussionmentioning
confidence: 71%
“…been suggested that sodium arsenite can activate PI3K in some cell types, we investigated the role of this pathway in sodium arsenite-induced HIF-1␣ protein accumulation and VEGF expression in OVCAR-3 cells (48). PI3K-mediated activation of Akt-1, the most frequently studied isoform of Akt, involves phosphorylation on its amino acid residues Ser 473 and Thr 308 .…”
Section: Induction Of Hif-1␣ Protein and Vegf Expression By Sodium Armentioning
confidence: 99%
“…These studies used high concentrations of arsenicals that are cytotoxic for most cell types. Here, PAO (50 μM) or iAs III (200-1000 μM) have been shown to stimulate basal, insulin-independent, glucose uptake in baby hamster kidney (BHK) cells (Pasternak et al, 1991;Sviderskaya et al, 1996;Warren et al, 1986;Widnell et al, 1990), bovine chromaffin cells (Fladeby and Serck-Hanssen, 1999), 3T3-L1 adipocytes (Bazuine et al, 2004;Bazuine et al, 2003;Gould et al, 1989) and in L6 myotubes (McDowell et al, 1997). A modest 1-3 fold increase in basal glucose uptake was typically found with no effect on the translocation of GLUT4, an insulin-sensitive glucose transporter, to the plasma membrane.…”
Section: Laboratory Studies Of the Effects Of As On Glucose Metabolismmentioning
confidence: 99%
“…Increased PI-3K-mediated PKB/Akt phosphorylation has been reported in cells exposed to toxic concentrations (200-500 μM) of iAs III (McDowell et al, 1997;Souza et al, 2001). Stress-induced phosphorylation of PKB/Akt is associated with the activation of pro-survival mechanisms aimed at preventing apoptosis and promoting cell proliferation (Dudek et al, 1997;Ibuki and Goto, 2000;Zhou et al, 2000).…”
Section: Laboratory Studies Of the Effects Of As On Glucose Metabolismmentioning
confidence: 99%
“…Subcellular Fractionation of L6 Myotubes-Subcellular membranes from L6 myotubes were isolated as described previously (21)(22)(23)(24). Briefly, 2 h prior to fractionation, cells were washed, and growth medium (containing 5 mM glucose) was supplemented with chloroquine (100 M).…”
Section: Methodsmentioning
confidence: 99%